Development of Phantom Limb Pain after Femoral Nerve Block - Sadiah Siddiqui; Anthony N. Sifonios; Vanny Le; Marc E. Martinez; Jean D. Eloy; Andrew G. Kaufman (Case Reports in Medicine)
Historically, phantom limb pain (PLP) develops in 50–80% of amputees and may arise within days following an amputation for reasons presently not well understood. Our case involves a 29-year-old male with previous surgical amputation who develops PLP after the performance of a femoral nerve block. Although there have been documented cases of reactivation of PLP in amputees after neuraxial technique, there have been no reported events associated with femoral nerve blockade. We base our discussion on the theory that symptoms of phantom limb pain are of neuropathic origin and attempt to elaborate the link between regional anesthesia and PLP. Further investigation and understanding of PLP itself will hopefully uncover a relationship between peripheral nerve blocks targeting an affected limb and the subsequent development of this phenomenon, allowing physicians to take appropriate steps in prevention and treatment.